2021
DOI: 10.3389/fbioe.2021.771133
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge on Polyethylene Terephthalate Degradation by Genetically Modified Microorganisms

Abstract: The global production of polyethylene terephthalate (PET) is estimated to reach 87.16 million metric tons by 2022. After a single use, a remarkable part of PET is accumulated in the natural environment as plastic waste. Due to high hydrophobicity and high molecular weight, PET is hardly biodegraded by wild-type microorganisms. To solve the global problem of uncontrolled pollution by PET, the degradation of plastic by genetically modified microorganisms has become a promising alternative for the plastic circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 77 publications
(147 reference statements)
0
22
0
Order By: Relevance
“…It is noteworthy to mention here that enzymatic recycling offers a greener avenue to depolymerizing and recycling PET waste [ 8 , 81 ]. This is because enzymatic PET recycling offers several benefits over chemical depolymerization.…”
Section: Biodegradation Of Petmentioning
confidence: 99%
See 4 more Smart Citations
“…It is noteworthy to mention here that enzymatic recycling offers a greener avenue to depolymerizing and recycling PET waste [ 8 , 81 ]. This is because enzymatic PET recycling offers several benefits over chemical depolymerization.…”
Section: Biodegradation Of Petmentioning
confidence: 99%
“…Conversely, CALB could transform MHET into TPA but exhibited a lower efficiency when used alone to hydrolyze PET [ 74 ]. The two lipases were seen to work synergistically to enhance PET hydrolysis following their complementary properties both in catalysis patterns and substrate specificity [ 8 , 143 ]. That said, the findings showed that the enzymes make ideal bioagents for the future biodegradation of plastics.…”
Section: Pet-degrading Enzymes For Pet Degradationmentioning
confidence: 99%
See 3 more Smart Citations